Information and data protection within a RDBMS - Khmelevsky, Y. (Condensed Matter Physics, 2008)
Security issues for some special large data, such as binary and image files, as well as video and audio files and streams still require a special development, especially for the industrial database systems (Oracle, MS SQL, DB2, etc). New encryption methods should be used additionally to traditional encryption methods and other protection solutions, such as authentication, authorization, access control, security monitoring and audit. The purpose of this article is to present the research results regarding information security and data protection, as well as some practical aspects of the encryption by CrypTIM algorithm, developed by Prof. V. Ustimenko in the last decade [Ustimenko V., Lecture Notes In Computer Science, 2001, 278, 2227]. This text additionally proposes a practical utilization of the Model Driven system design for large objects (LOB) encryptions within a database, used to store some special large binary files, such as images, sound files, movies, special binary files in order to improve maintenance and data protection. Novel problems and trends in providing security against criminal activities in the current Cyberspace are analyzed.